GUAVA LEAVES, CORN COBS, AND MANGOSTEEN PEELS AS ANTIOXIDANTS AND NATIONAL STANDARDIZED NATURAL PRESERVATIVES FOR COCONUT BROWN SUGAR - ADITYA PRATAMA PUTRA; KINTAN NUR ROMADHONA; ROSIANA SOFIA ANGGRAENI; AI RIAN JULYANTI; RETNO FITRI WIDIASTUTI; DINIATIK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Below standard brown sugar is a sugar that cannot be made or resembles dodol (a traditional and sticky confection) because the sap is damaged. Although the sap is made into brown sugar, the product will not last long and become soft-textured sugar. The aim of this research is to prevent below standard sap and produces coconut sugar in accordance with Indonesian National Standard (SNI) using natural preservatives were formulated from guava leaves, corn cobs, and mangosteen peels. Methods: The formulation of guava leaves, corn cobs, and mangosteen peels was designed through several stages by testing the composition of the materials. The first step was measuring the pH value of each material with concentration 4.5%, which were 4.5 g per material and it was compared to the composition of the formula after the concentration of each material was combined to get the basis pH. The second step was formulation to get the natural preservatives by applying the formulas on the tap process of sap until the manufacturing process to get the coconut sugar. Quality of coconut sugar was conducted SNI 01-3743-1995 which included oven method for testing water content and insoluble parts, Luff schoorl method for reducing sugar content and sucrose, and atomic absorption spectroscopy method for testing the contamination of Cu metal. Results: Guava leaves, corn cobs, and mangosteen peels with each material 4.5% were the optimal concentrations as natural preservatives to inhibit fermentation process of sap. Coconut sugars were obtained using these natural preservatives. Coconut sugar that obtained had the moisture content was 0.2402%, the ash content was 1.3%, reducing sugar content was 0.39%, the sucrose level was 69.99%, and the metal contamination was 0.201 mg/kg Cu. While the results of organoleptic tests indicated the brownish-yellow sugar, a typical sweet taste of sugar, and the normal smell of coconut sugar. All of the coconut sugar properties were meet with SNI. Conclusion: Guava leaves, corn cobs, and mangosteen peels were effective as natural preservatives and antioxidants to produce the best quality of coconut sugar according to the SNI.